1996
DOI: 10.1177/095632029600700201
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B: New Approaches for Antiviral Chemotherapy

Abstract: SummaryProgress in the development of effective therapeutic regimes for chronic hepatitis B has been slow, mainly due to the lack of promising lead compounds and useful assays for high throughput in-vitro screening. Nucleoside analogue chemotherapy has targeted the inhibition of the hepatitis B virus (HBV) polymerase and achieved inhibition of this unique viral enzyme. The persistence and resistance of HBV covalently closed circular (or supercoiled) DNA, the key replicative intermediate and sole transcriptiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 59 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…9 This pool of transcriptional templates appears to be very stable and studies by Summers et al using the duck hepatitis B virus (DHBV), have shown that the level of viral cccDNA is regulated by the pre-S envelope proteins via negative feedback. 10 Thus, early in infection when there are low amounts of surface envelope proteins, mature nucleocapsids are shunted into the nucleus whereby the newly synthesized viral genome is converted into cccDNA.…”
Section: Regulation Of Hepadnaviral Cccdna: Role Of the Viral Envelopementioning
confidence: 99%
“…9 This pool of transcriptional templates appears to be very stable and studies by Summers et al using the duck hepatitis B virus (DHBV), have shown that the level of viral cccDNA is regulated by the pre-S envelope proteins via negative feedback. 10 Thus, early in infection when there are low amounts of surface envelope proteins, mature nucleocapsids are shunted into the nucleus whereby the newly synthesized viral genome is converted into cccDNA.…”
Section: Regulation Of Hepadnaviral Cccdna: Role Of the Viral Envelopementioning
confidence: 99%
“…ETV and the other three other approved nucleoside analogs lamivudine (3TC), adefovir dipivoxil (ADV), and telbivudine also target the HBV polymerase (Pol), which is essential to viral replication. Pol is responsible for converting the plus-strand pre-genomic RNA into a partially double-stranded circular DNA genome during a multistep process (1)(2)(3). ETV-5Ј monophosphate is incorporated by HBV Pol resulting in inhibition of the protein-linked priming activity, the reverse transcription of the pre-genomic mRNA, and the DNA-directed DNA synthesis activities of HBV Pol (4).…”
Section: Entecavir (Etv)mentioning
confidence: 99%
“…4,42 Cessation of therapy with nucleoside analogs, in particular, has usually resulted in reversion of viral replication to at least pretreatment rates-the relapse phenomenon, which is most probably caused by intracellular persistence of HBV CCC DNA 21,23,41 -and persistence of virus in nonhepatocyte reservoirs. 25,30 Nowak et al 41 recently calculated that, on the basis of estimates of rates of viral and hepatocyte turnover, 1 year of continuous treatment with an effective nucleoside analog such as 3TC could, at best, result in complete elimination of HBV, and even, at worst, could reduce the frequency of infected hepatocytes to about 8%.…”
Section: Discussionmentioning
confidence: 99%
“…This situation the PDH test system, particularly with DHBV covalently closed could be expected to mimic the in vivo end-of-treatment situation circular (CCC) DNA, the replicative species most resistant to when residual nucleoside analog and virus are both present and antiviral therapy. 4,21 ''rebound'' (i.e., resumption of viral replication to at least pretreatment levels) commonly occurs. 23 Uninfected PDH cultures were MATERIALS AND METHODS prepared as described above and allowed to attach overnight before exposure for 24 hours to halving dilutions of 3TC and PCV (alone Drugs and Chemicals.…”
Section: Moval Furthermore the Combination Was More Effective Inmentioning
confidence: 99%
See 1 more Smart Citation